Endocranial morphology of Auroraceratops sp. (Dinosauria: Ceratopsia) from the Early Cretaceous of Gansu Province, China. (25th November 2020) - Zhang, Qian-Nan; King, James L.; Li, Da-Qing; Hou, Ye-Mao; You, Hai-Lu
ABSTRACT: Fossils of Auroraceratops are abundant and found in high concentrations within the Mazongshan area of northwestern China. As small basal Neoceratopsia discovered from the Lower Cretaceous, its general anatomy is well known; however, the endocranial morphology of this genus has never been formally described before. Here, we selected a well-preserved skull which belongs to Auroraceratops sp. and used a high-resolution CT scan to reconstruct its three-dimensional, virtual endocast in order to illustrate the endocranial structures in detail. Our study provides the first description of the endocranial anatomy of Auroraceratops and compares it with other relevant ceratopsian taxa. Our result shows that for a basal Neoceratopsia, the endocranial morphology of Auroraceratops is closer to that of non-neoceratopsian ceratopsian Psittacosaurus than the more derived neoceratopsians, such as Pachyrhinosaurus, which provides new insight into the endocranial characters of basal Neoceratopsia.